A CT-FFR-guided unroofing procedure for repairing the anomalous origin of the left coronary artery—a case report - Zuo, Hairun; Xu, Chengyi; Wang, Li; Liu, Chengwei; Liu, Li; Su, Xi (Frontiers in Cardiovascular Medicine, 2023)
Anomalous aortic origin of a coronary artery (AAOCA) is a common congenital coronary artery malformation which includes several subtypes. It is one of the main causes of sudden cardiac death (SCD) in youths, especially competitive athletes. The accurate diagnosis and identification of high-risk patients with AAOCA referral for surgical repair can save those patients’ lives. However, current diagnostic tools, such as invasive angiography, echocardiography and intravascular ultrasound (IVUS) have known limitations in visualizing coronary orifices and characterizing vessels. In this study, we reported a 14-year-old adolescent who suffered from repeated syncope during exercise. Using computed tomography - fractional flow reserve (CT-FFR) technique, AAOCA was diagnosed which revealed his left coronary artery (LCA) originated from right Valsalva sinus and run between the aorta and pulmonary artery with an intra-arterial wall course (~ 20mm in length), with abnormal FFR of LCA at rest. Patient was referred for unroofing surgery and repeated CT-FFR showed significantly improved FFR of LCA. Patient resumed to normal physical activity without syncope recurrence. In this report, we highlighted the usefulness of CT-FFR as a non-invasive, feasible and effective tool in guiding whether a patient with AAOCA requires surgical revascularization, and in evaluating the effectiveness after surgery.